ANALYTIC PROGNOSTICAION OF SENSITIVITY OF STAPHYLOCOCCUS TO FLUOROQUINOLONES - Палій, Г.К.; Назарчук, О.А.; Нагайчук, В.І.; Осадчук, Н.І.; Палій, Д.В.; Коваленко, І.В. (World of Medicine and Biology, 2015)
In the research the new data of Staphylococcus clinical strains’ sensitivity to fluoroquinolones are presented. The aim of the research was to carry out analytic prognosis of sensitivity of S. aureus to fluoroquinolones, isolated from patients. Materials and methods. The research was held during the period of 2011-2015 years, in which 380 patients with purulent-inflammatory complications took part. Patient with burn trauma were treated according to standard management guidelines, having received antimicrobial treatment (antibiotics, antiseptics). From patients there were isolated 143 clinical strains of S. aureus (2011 р. – n=37; 2012 р. – n=25; 2013 р. – n=27; 2014 р. – n=26; 2015 р. – n=28). There was studied the sensitivity of S. aureus to ciprofloxacin, levofloxacin, gatifloxacin, moxifloxacin by means of standard disc-diffusion method on dense medium. By means of mathematical methods of statistic prognostication the analytical dependence of dynamic prognostic changing criteria of S. aureus clinical strains’ sensitivity to fluoroquinolones of different generations were obtained. Prognostic mathematical models were conducted. Authenticity of every model and substantiation of the prognosis of antibiotic sensitivity of S. aureus were estimated due to determination criteria (r2). The statistic analysis was carried out with “STATISTICA 7”; “Matlab 7.11”. Results and their discussion. In the result of the statistic analysis of obtained in the research data we found decreasing sensitivity of S. aureus to ciprofloxacin. Mathematical extrapolation of previous normality testifies low sensitivity of Staphylococcus to ciprofloxacin in future. The analysis of smoothed data series (2011-2015 years) of S. aureus sensitivity have shown its increasing linear tendency to levofloxacin. Mathematical analysis of five year research gave the possibility to conduct prognostic model of S. aureus sensitivity to gatifloxacin. According to which we found step by step retrieval sensitivity to gatifloxacin in Staphylococi, colonizing burn wounds. But further analysis have forecast decreasing the sensitivity of S. aureus to this drug in near future. Prognosis of the level of S. aureus sensitivity, isolated from burn wounds in patients proved the its retrieving moxifloxacin. Forecasting data of its sensitivity was near 92,5 %. Conclusion. Obtained analytical prognostication formulas of S. aureus sensitivity to fluoroquinolones prove the decreasing effectiveness of ciprofloxacin against Staphylococcus; show tendency of optimizing sensitivity to levofloxacin; high sensitivity of S. aureus to moxifloxacin (92,5 %), gatifloxacin (94 %).